Surge forces of a FPSO at Lee side of submerged plate in regular waves - Priyanto, Agoes (2008)
A submerged horizontal plate type breakwater is not only to be good energy dissipates of wave breaking on the top of the plate, but also to generate steady flow and to reproduce shorter waves. This paper assessed a submerged plate which is applied to set up for an Oil/Gas Floating Production Storage and Offloading (FPSO) structure. The wave exciting surge forces of the FPSO at the lee side of the submerged plate were examined by using Boundary Element Method based on the potential theory. In order to verify the numerical results, the model experiments have been carried out in Towing Tank of Laboratorium Hidrodinamika Indonesia, BPP Teknologi. By comparing the numerical results with the experimental ones, the results show that the numerical results have similar tendency to the experimental ones, and it is deduced that the submerged plate reduces effectively the wave exciting surge forces at low wave frequencies.